Frontiers in positron emission tomography imaging of the vulnerable atherosclerotic plaque. Issue 14 (24th June 2019) - MacAskill, Mark G; Newby, David E; Tavares, Adriana A S
Abstract: Rupture of vulnerable atherosclerotic plaques leading to an atherothrombotic event is the primary driver of myocardial infarction and stroke. The ability to detect non-invasively the presence and evolution of vulnerable plaques could have a huge impact on the future identification and management of atherosclerotic cardiovascular disease. Positron emission tomography (PET) imaging with an appropriate radiotracer has the potential to achieve this goal. This review will discuss the biological hallmarks of plaque vulnerability before going on to evaluate and to present PET imaging approaches which target these processes. The focus of this review will be on techniques beyond [ 18 F]FDG imaging, some of which are clinically advanced, and others which are on the horizon. As inflammation is the primary driving force behind atherosclerotic plaque development, we will predominantly focus on approaches which either directly, or indirectly, target this process.